2010
DOI: 10.1002/jnr.22340
|View full text |Cite
|
Sign up to set email alerts
|

NRAGE is a negative regulator of nerve growth factor‐stimulated neurite outgrowth in PC12 cells mediated through TrkA‐ERK signaling

Abstract: NRAGE, also denominated as MAGE-D1 or Dlxin-1, is firstly identified as a molecule interacting with NGF low affinity receptor p75NTR. It facilitates cell cycle arrest and NGF-dependent neuronal apoptosis. Here we report that NRAGE is downregulated while p75NTR is upregulated during the process of NGF-induced neuronal differentiation of PC12 cells. Knockdown of NRAGE by RNA interference accelerates NGF-mediated neurite outgrowth. In addition, in the NRAGE-suppressed cells, NGF-induced ERK activation is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…On the other hand, Feng et al . have reported opposite effects, seeing a reduction of neuronal differentiation and associated ERK signalling after NRAGE overexpression and an increased NGF-induced ERK activation after knocking down NRAGE [28]. Moreover, previous studies have demonstrated that p75 NTR -mediated apoptosis – rather than differentiation – is facilitated by NRAGE in various cell types including PC12 [24], [27] and that Praja1 targets various anti-apoptotic factors [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Feng et al . have reported opposite effects, seeing a reduction of neuronal differentiation and associated ERK signalling after NRAGE overexpression and an increased NGF-induced ERK activation after knocking down NRAGE [28]. Moreover, previous studies have demonstrated that p75 NTR -mediated apoptosis – rather than differentiation – is facilitated by NRAGE in various cell types including PC12 [24], [27] and that Praja1 targets various anti-apoptotic factors [13].…”
Section: Discussionmentioning
confidence: 99%
“…NRAGE is highly expressed in the developing and adult nervous system, often but not exclusively together with p75 NTR [23], [24]. NRAGE has been shown to be pro-apoptotic in various cell types [24][27] and to be involved in the neuronal differentiation of pheochromocytoma (PC12) cells [28], [29]. PC12 cells endogenously express the NRAGE activator p75 NTR [24], which is known to mediate NGF-signalling in cell survival, differentiation and cell death [18], [24].…”
Section: Introductionmentioning
confidence: 99%
“…NRAGE suppresses metastasis of melanoma and pancreatic cancers in vivo and in in vitro studies ; NRAGE also promotes proliferation of oesophageal carcinoma cells . Meanwhile, NRAGE provides endogenous regulation of neuronal proliferation and differentiation of PC12 cells . According to previous studies, NRAGE modulates function of Dlx/Msx to promote myogenic differentiation and strong NRAGE mRNA signals have been found in cell layers surrounding cartilaginous elements in bone rudiments, during digit formation in embryogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…The role of NRAGE in neuronal growth is less clear; in PC12 cells, both growth-suppressing (Feng et al, 2010) and growth-promoting effects have been reported (Reddy et al, 2010), while in NRAGE knockout mice neuronal growth was found to be normal (Bertrand et al, 2008).…”
Section: Discussionmentioning
confidence: 99%